Work Fatigue as a Mediator in the Influence of Communication and Assertivity on Nurses' Productivity - Rosida Siboro; Andry Andry; MF Arrozi Adhikara (International Forum of Researchers and Lecturers, 2026)
Rapid global environmental changes, especially due to advances in technology and information, have had a significant impact on various sectors of life, including the health sector. In the context of modern health services, hospitals are no longer just places of healing, but also institutions that are required to provide high-quality services, based on patient safety, and are able to adapt to the dynamics of community needs. This change requires a transformation in human resource management, especially related to the interpersonal and psychosocial competencies of nurses as the spearhead of medical services.Purposes:​ to analyze the effect of effective communication and Assertive Attitude on Nurses' Work Productivity in hospitals, with Work Fatigue as a mediating variable.Methods: This type of research is quantitative, using statistical figures to measure the influence of independent variables on dependent variables. The research design is a cross-sectional study.Results: The results of this study indicate that effective communication, assertiveness, and job fatigue collectively significantly influence nurses' work productivity. Communication and assertiveness positively contribute to job fatigue, which in turn affects productivity. Job fatigue is also shown to be a significant mediator in the relationship between communication and assertiveness on work productivity .Conclusion : The importance of strengthening effective communication as a strategy to increase productivity. Organizations need to design communication systems that support openness, transparency, and clarity of information and culture-based assertiveness training, so that employees can express their opinions appropriately without causing resistance in the team.